Pelvic and acetabular trauma in amateur equestrian enthusiasts – A retrospective review. Issue 3 (June 2022) - Francis, A.O.; McCabe, F.; McCabe, P.; O'Daly, B.J.; Leonard, M.
Abstract: Introduction: Horse riding related accidents can present with devastating pelvic and acetabular fractures. This study examines the nature, management and treatment outcomes of severe pelvic and acetabular trauma in amateur horse riders presenting to a national tertiary referral centre. We also aim to define certain at-risk groups. Methods: This was a retrospective descriptive cohort of all patients who were referred to the National Centre for Pelvic and Acetabular trauma resulting from horse riding accidents. All patients who were referred to the National Centre for Pelvic and Acetabular Trauma between January 2018 and July 2020 were included. Professional horse riders were excluded. Clinical and treatment outcome measures were stratified to four different mechanisms of injury: fall from horse (FFH), horse crush (HC), Horse Kick (HK) and Saddle Injury (SI). Results: There were 31 equestrian related injuries referred to our centre between January 2018 and July 2020. One patient was a professional jockey and was thus excluded from the study. Eighteen were female and the mean age at referral was 37 years old. The majority of these were pelvic ring injuries (73%). Fifty per cent of patients required surgical intervention and the majority of these were male. Conclusion: Horse riding is a potentially dangerous recreational pursuit with significant risk of devastating injury. Pelvic and acetabular fractures secondary to horse riding are frequently associated with other injuries and the need operative intervention is common in this group. Young women and older men are higher risk groups. Highlights: Horse riding has the potential for devastating injuries in the amateur community. Pelvic injuries are more common than acetabular injuries. Young women and older men are at-risk groups for pelvic and acetabular injury. Men are more likely to require surgery after such an injury. Adequate education on fall techniques as well as protective equipment is needed.